If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3n + 5)(4n + 5) = 0 Reorder the terms: (5 + 3n)(4n + 5) = 0 Reorder the terms: (5 + 3n)(5 + 4n) = 0 Multiply (5 + 3n) * (5 + 4n) (5(5 + 4n) + 3n * (5 + 4n)) = 0 ((5 * 5 + 4n * 5) + 3n * (5 + 4n)) = 0 ((25 + 20n) + 3n * (5 + 4n)) = 0 (25 + 20n + (5 * 3n + 4n * 3n)) = 0 (25 + 20n + (15n + 12n2)) = 0 Combine like terms: 20n + 15n = 35n (25 + 35n + 12n2) = 0 Solving 25 + 35n + 12n2 = 0 Solving for variable 'n'. Factor a trinomial. (5 + 3n)(5 + 4n) = 0Subproblem 1
Set the factor '(5 + 3n)' equal to zero and attempt to solve: Simplifying 5 + 3n = 0 Solving 5 + 3n = 0 Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3n = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3n = 0 + -5 3n = 0 + -5 Combine like terms: 0 + -5 = -5 3n = -5 Divide each side by '3'. n = -1.666666667 Simplifying n = -1.666666667Subproblem 2
Set the factor '(5 + 4n)' equal to zero and attempt to solve: Simplifying 5 + 4n = 0 Solving 5 + 4n = 0 Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4n = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4n = 0 + -5 4n = 0 + -5 Combine like terms: 0 + -5 = -5 4n = -5 Divide each side by '4'. n = -1.25 Simplifying n = -1.25Solution
n = {-1.666666667, -1.25}
| -6x+1=-3(2x+1)+x | | 6y+11=43 | | X^2-15x+12=-6+4 | | 5x-3(x-1)-39= | | (2+3c)(4+6c+9c)= | | (2a-1)(a+3a+5)= | | 435*13= | | X+3=-3-5 | | 46.1*46.1=18.5*18.5+2(11.17)x | | 2(3x-5)=-(x-11) | | 2s-2=2 | | (a+2a-9)(a+3)= | | -15.00+2.00w=5 | | 12+7y-2=52 | | (y+3y-6)(2y+3)= | | 0=2x^2+6kx+8 | | 7r^2-14r-7=0 | | A=5W+10Z | | 2.00r-15.00=9 | | 12x-8=16x+4 | | 4x^2-3=x^2-11x | | (3x+2y)(2y+3x)= | | -4g+6=14 | | 6(x)-x=0 | | (z-2x)(z-2x)= | | 0.015x-0.030=0.030 | | 76=b+4 | | 3y(2+4y+5y^2)= | | 4(x-5)-7-5(3-2x)= | | (a+b)(2a-3b)= | | g-92=-74 | | (7y-4t)(2y+5t)= |